Validating DNA Polymorphisms Using KASP Assay in Prairie Cordgrass (Spartina pectinata Link) Populations in the U.S. - Graves, Hannah; Rayburn, A. L.; Gonzalez-Hernandez, Jose L.; Nah, Gyoungju; Kim, Do-Soon; Lee, D. K. (Frontiers in Plant Science, 2016)
Single nucleotide polymorphisms (SNPs) are one of the most abundant DNA variants found in plant genomes and are highly efficient when comparing genome and transcriptome sequences. SNP marker analysis can be used to analyze genetic diversity, create genetic maps, and utilize marker-assisted selection breeding in many crop species. In order to utilize these technologies, one must first identify and validate putative SNPs. In this study, 121 putative SNPs, developed from a nuclear transcriptome of prairie cordgrass (Spartina pectinata Link), were analyzed using KASP technology in order to validate the SNPs. Fifty-nine SNPs were validated using a core collection of 38 natural populations and a phylogenetic tree was created with one main clade. Samples from the same population tended to cluster in the same location on the tree. Polymorphisms were identified within 52.6% of the populations, split evenly between the tetraploid and octoploid cytotypes. Twelve selected SNP markers were used to assess the fidelity of tetraploid crosses of prairie cordgrass and their resulting F2population. These markers were able to distinguish true crosses and selfs. This study provides insight into the genomic structure of prairie cordgrass, but further analysis must be done on other cytotypes to fully understand the structure of this species. This study validates putative SNPs and confirms the potential usefulness of SNP marker technology in future breeding programs of this species.